B cells promote obesity-associated periodontitis and oral pathogen-associated inflammation. Issue 2 (29th April 2014) - Zhu, Min; Belkina, Anna C; DeFuria, Jason; Carr, Jordan D; Van Dyke, Thomas E; Gyurko, Robert; Nikolajczyk, Barbara S
Abstract : B cells promote bone loss and inflammation in obesity-associated periodontitis, but play a modest role in periodontitis of lean hosts. Abstract: Individuals with T2D and PD suffer significantly from the ability of one disease to intensify the other. Disease-associated inflammation is one mechanism thought to fuel this pathogenic feed-forward loop. Several lines of evidence indicate that proinflammatory B cells promote T2D and PD; thus, B cells are top candidates for a cell type that predisposes PD in T2D. To test directly the role of B cells in T2D-associated PD, we compared outcomes from oral Porphyromonas gingivalis challenge of lean WT or B cell-null mice with outcomes from mice that were obese and insulin-resistant before challenge. Obese WT mice responded to oral P. gingivalis challenge with significant periodontal bone loss, whereas obese B cell-null mice were protected completely from PD. By contrast, lean WT and B cell-null mice suffer similar periodontal bone loss in response to oral pathogen. B cells from obese/insulin-resistant hosts also support oral osteoclastogenesis and both oral and systemic production of inflammatory cytokines, including pro-osteoclastogenic TNF-α and MIP-2, an ortholog of human IL-8. B cells furthermore impact AT inflammation in obese, P. gingivalis -infected hosts. Taken together, these data show that fundamentally different mechanisms regulate PD in lean and obese hosts, with B cells able to promote PD only if the hosts are "primed" by obesity. These results justify more intense analysis of obesity-associated changes in B cells that predispose PD in human T2D.